Differenzielles Torschusstraining im Fußball - Trockel, M.; Schöllhorn, W. I. (Messplätze, Messplatztraining, motorisches Lernen: ausgewählte Beiträge; 5. gemeinsames Symposium der dvs-Sektionen Biomechanik, Sportmotorik und Trainingswissenschaft; Universität Leipzig, Sportwissenschaftliche Fakultät, 19. bis 21. September 2002 / Veranst.: Sportwissenschaftliche Fakultät der Universität Leipzig ..., 2003)
The investigation compares the efficiency of a new concept called `differencial training` with a traditional concept of training in soccer for a goal kicking movement. In a pre-post-retentiontest design 20 skilled soccer players were trained in two groups with 10 test subjects. Group 1 trained the goal kicking movement with a traditional concept based on conventional methodical series of exercises. Group 2 trained according to the new conception `differencial learning` were mainly no movement is repeated twice. The results indicate that, through differencial training even on a skilled level greater progress in motor learning can be achieved.